Quiver Belt Fasteners from Developed Middle Age Burials in the Kuznetsk Basin - Andrey M. Ilyushin; Marat G. Suleymenov (Археология евразийских степей, 2022)
The paper addresses the fasteners used to attach a quiver to a battle belt based on developed Middle Age materials from the Kuznetsk Basin. Quiver loops, pads, braces and hooks are subjected to typological classification, comparative analysis, dating and ethnocultural characterization. Five groups and thirteen types of products are distinguished, dated at different intervals within the 11th–14th centuries. The bulk of the finds belong to the archeological and ethnographic complex of burials conducted using an ingumation ritual with a carcass or skin of a horse, and the Shandin archaeological culture identified with the Kypchak culture. It is concluded that the use of quiver fasteners in the territory of the Kuznetsk Basin during the developed Middle Ages reflects the general dynamics of the development of similar products in steppe and forest-steppe Eurasia.